2021
DOI: 10.3892/mmr.2021.12163
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Txk‑mediated activation of NF‑κB signaling pathway on neurological deficit and oxidative stress after ischemia‑reperfusion in rats

Abstract: Ischemic stroke is an extremely mortal cerebrovascular disease, and neuroinflammation and oxidative stress emerge as important traits of ischemic stroke. However, as an inflammation-associated factor, Txk tyrosine kinases (Txk) has been poorly studied in neuroscience research. The aim of the present study was to investigate the role of Txk after ischemia-reperfusion (I/R) in vivo and in vitro , observe the association between Txk knockdown and neurological deficit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…After cerebral I/R injury, the generation of ROS increases, creating an imbalance between production and clearance that triggers inflammation and cell death by mutilating proteins, DNA, and RNA . Many antioxidants lessen cerebral I/R injury, strongly suggesting that the regulation of oxidative stress is an appealing prospective therapeutic target for minimizing cerebral I/R injury. , After cerebral I/R damage, oxygen free radicals are created, SOD viability is lowered, and the MDA concentration is raised, leading to lipid peroxidation, which further inhibits nerve cell function and causes brain damage. , It was discovered that administering LZWL02003 to LPS-stimulated microglia inhibited the increase in ROS and, consequently, the inflammatory response . However, no previous research has indicated that LZWL02003 can lessen the oxidative damage induced by cerebral I/R.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After cerebral I/R injury, the generation of ROS increases, creating an imbalance between production and clearance that triggers inflammation and cell death by mutilating proteins, DNA, and RNA . Many antioxidants lessen cerebral I/R injury, strongly suggesting that the regulation of oxidative stress is an appealing prospective therapeutic target for minimizing cerebral I/R injury. , After cerebral I/R damage, oxygen free radicals are created, SOD viability is lowered, and the MDA concentration is raised, leading to lipid peroxidation, which further inhibits nerve cell function and causes brain damage. , It was discovered that administering LZWL02003 to LPS-stimulated microglia inhibited the increase in ROS and, consequently, the inflammatory response . However, no previous research has indicated that LZWL02003 can lessen the oxidative damage induced by cerebral I/R.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 After cerebral I/R damage, oxygen free radicals are created, SOD viability is lowered, and the MDA concentration is raised, leading to lipid peroxidation, which further inhibits nerve cell function and causes brain damage. 33,34 It was discovered that administering LZWL02003 to LPS-stimulated microglia inhibited the increase in ROS and, consequently, the inflammatory response. 10 However, no previous research has indicated that LZWL02003 can lessen the oxidative damage induced by cerebral I/R.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In transient global cerebral ischemic stroke, sudden cerebral blood flow is occluded, causing a lack of oxygen and glucose supply to brain tissues leading to irreparable neuronal injury [ 4 ]. Transient global cerebral ischemic stroke is a life-threatening cerebrovascular disease in which neuroinflammation and oxidative stress are prominent features [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…When this balance is altered by abnormal stimuli, cells may undergo oxidative stress, leading to the production of a huge amount of reactive oxygen species (ROS) by mitochondria [ 6 ]. Excessive production of ROS (including the superoxide radical, O 2 · − ) contributes to neuronal cell damage by disrupting cell membranes, damaging DNA, and triggering cellular apoptosis [ 7 , 8 , 9 ]. Antioxidant superoxide dismutase enzymes (SODs) are able to convert O 2 · − into hydrogen peroxide (H 2 O 2 ) and oxygen (O 2 ).…”
Section: Introductionmentioning
confidence: 99%